2010
DOI: 10.1038/aps.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Open channel block of Kv1.5 currents by citalopram

Abstract: Aim: To examine whether selective serotonin reuptake inhibitor citalopram interacts with Kv1.5, one of the cardiovascular-specific Kv channel isoforms. Methods: The interaction between citalopram and Kv1.5 expressed in Chinese hamster ovary cells was studied using the whole-cell patch-clamp technique. Results: Citalopram reduced Kv1.5 whole-cell currents in a reversible concentration-dependent manner, with an IC 50 value and a Hill coefficient of 2.8±1.1 µmol/L and 0.8±0.3, respectively. Citalopram-induced inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
1
9
2
Order By: Relevance
“…It has been, however, reported that citalopram may lead to cardiovascular risk, for example QT prolongation, within the clinical concentration range (26), whereas the relation between Kv1.5 inhibition and QT prolongation is not completely clear. The IC 50 value of citalopram for Kv1.5 obtained by the post-ES viability assay (1.5 mM) was comparable to that determined electrophysiologically in the precedent study (2.8 mM) (17) but slightly lower than that obtained electrophysiologically in this study (at the pulse end: 7.48 mM). Taken together, it is notable that citalopram showed Kv1.3 block and the IC 50 s for Kv1.3 were roughly comparable to those for Kv1.5.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It has been, however, reported that citalopram may lead to cardiovascular risk, for example QT prolongation, within the clinical concentration range (26), whereas the relation between Kv1.5 inhibition and QT prolongation is not completely clear. The IC 50 value of citalopram for Kv1.5 obtained by the post-ES viability assay (1.5 mM) was comparable to that determined electrophysiologically in the precedent study (2.8 mM) (17) but slightly lower than that obtained electrophysiologically in this study (at the pulse end: 7.48 mM). Taken together, it is notable that citalopram showed Kv1.3 block and the IC 50 s for Kv1.3 were roughly comparable to those for Kv1.5.…”
Section: Discussionsupporting
confidence: 79%
“…Effects of acacetin and citalopram on Kv1.5 channels currents have been reported based on electrophysiological results in a heterologous expression system (17,18). However, the effects were also determined in this study using HEK293 cells heterologously expressing Kv1.5 alone under the same experimental conditions for Kv1.3 channel current measurements in Fig.…”
Section: Effects Of Acacetin and Citalopram On Membrane Currents Thromentioning
confidence: 85%
See 1 more Smart Citation
“…, 2004). Similarly, citalopram has been found to inhibit the neuronal Kv 1.5 current (Lee et al. , 2010), the HERG‐K + current (Witchel et al.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, a number of unrelated compounds, such as CaMK II blockers (2-[N-(2-hydroxyethyl)]-N-(4methoxybenzenesulfonyl)] amino-N-(4-chlorocinnamyl)-N-methylbenzylamine; KN-93), tyrphostin (tyrosine kinase inhibitor, AG-1478), citalopram (antidepressant), disopyramide, cytochalasin (actin-disrupting agent), or loratadine (non-sedating antihistamine), also act directly on Kv1.5 [103][104][105][106][107][108]. However, their pharmacological uses targeting cell proliferation are debatable.…”
Section: Kv15mentioning
confidence: 99%